ZnO nanoparticles as reusable heterogeneous catalyst for efficient one pot three component synthesis of imidazo-fused polyheterocycles. Issue 12 (23rd March 2016) - Swami, Suman; Devi, Nisha; Agarwala, Arunava; Singh, Virender; Shrivastava, Rahul
Graphical abstract: Abstract: An efficient, simple, environmentally benign synthetic protocol is developed for synthesis of biologically and medicinally relevant pyrazole coupled imidazo[1, 2- a ]pyridine derivatives via three component reaction of alkyl-4-formyl-1-phenyl-1 H -pyrazole-3-carboxylate, 2-aminopyridine and isocyanide in the presence of nano-crystalline ZnO in ethanol through one pot chemical operation. The present synthetic protocol provides several advantages like operational simplicity, short reaction time, reusable catalyst, and easy work-up procedure.